Internal mimetic behavior of MNCs with respect to foreign subsidiary staffing. Issue 1 (9th March 2015) - Ando, Naoki
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to fill the following research gaps. First, few studies have examined isomorphic behavior of multinational corporations (MNCs) with respect to foreign subsidiary staffing. Second, the adoption by an MNC of its internally preferable practices, which is referred to as internal mimetic behavior, has been less extensively investigated when compared with the imitation of practices adopted by a large number of peer firms. Lastly, factors that facilitate internal mimetic behavior have not been extensively explored. Design/methodology/approach – This study hypothesizes that internal mimetic behavior is affected by both formal and informal institutional distance. The hypotheses are tested using the panel data set that consists of 3, 981 foreign subsidiaries of Japanese MNCs. Findings – This study finds that as the formal institutional distance between the host country and the home country increases, MNCs are more likely to adopt internal mimetic behavior. Furthermore, it demonstrates that as the informal institutional distance increases, the likelihood that MNCs adopt internal mimetic behavior decreases. Practical implications – This study suggests that MNCs need to consider the consequences of internal mimetic behavior when they adopt it without having economic rationale. It also suggests that when uncertainty can be mitigated, MNCs should avoid internal mimetic behavior. Originality/value – This study fills the aforementioned research gaps by examining what factors facilitate internal mimetic behavior. It suggests that both economic rationale and isomorphic behavior need to be considered to advance an understanding of foreign subsidiary staffing.